Cold agglutinin anti‐I antibodies in two patients with COVID‐19. Issue 9 (2nd August 2022) - Imoto, Hiroharu; Yoshioka, Satoshi; Nakagawa, Daishi; Hasegawa, Kohei; Kuroda, Hirokazu; Hasuike, Toshikazu; Doi, Asako; Kusumoto, Toshiko; Ishikawa, Takayuki
Abstract: Background: Cold agglutinin syndrome (CAS) is associated with various diseases. Several studies of CAS associated with coronavirus disease 2019 (COVID‐19) reported hemolytic anemia and thrombosis; however, the clinical significance of cold agglutinins (CA) in patients with COVID‐19 is unclear. Here, we present two cases of CA identified in the context of COVID‐19 without hemolytic anemia and clotting. Case report and Discussion: Two patients with no known risk factors for CA were diagnosed with COVID‐19; peripheral blood smears reveal red blood cells (RBCs) agglutination. These patients showed a high CA titer. We confirmed retrospectively that the CA was an anti‐I antibody. The two COVID‐19 cases with a high CA titer showed no hemolysis or thrombosis. Mycoplasma pneumoniae is known to cause CAS, but not all patients who have a high CA titer show hemolysis. Coagulation abnormalities are documented in severe COVID‐19 cases. Although CA increases the risk of thrombosis in those with lymphoproliferative diseases, the role of anti‐I antibodies in COVID‐19 is unclear. The impact of CAS on clinical presentations in COVID‐19 remains a matter of verification. Conclusions: A high CA titer was identified in COVID‐19 patients without hemolytic anemia and clotting. Anti‐I antibodies were identified. Further studies are required to clarify the pathophysiology of CA in COVID‐19.